MEDIA PEMBELAJARAN BERBASIS MEDIA AUDIO-VISUAL DAN MOTIVASI BELAJAR DALAM MENINGKATKAN MINAT PEMBELAJARAN FIQIH - Agustina, Kania; Wardana, Wardana; Fatimah, Fatimah (JURNAL AL-QAYYIMAH, 2023)
The advances in science and technology accelerate modernization in all areas, it grew stronger developments in line with the demands of reform and globalization. It is necessary for human resources which has the competence to master science and technology and be able to compete for the challenges of globalization. The development of science and technology (science and technology) can bring qualified human resources into all aspects of human life that can change the life style of the traditional mode of modern life. The changes that must be followed to improve the quality of human resources, one way to improve the quality of education. The national education system continues to be developed in accordance with the needs and developments in the local, national and global. Fiqh subjects closely related to the real world of students, for example thaharah, prayer, Hajj and Umrah, taking care of the corpse, sale and purchase, inheritance and others. For that a teacher must be creative in delivering course material, creating a fun learning conditions for students, so that students are interested and able to understand the material presented by the teacher to the fullest. The use of instructional media at the stage of learning orientation will greatly help the effectiveness of the learning process and the delivery of messages and content at the time. Besides, to encourage motivation and interests of students, learning media can also help students improve comprehension, presenting an interesting and reliable data facilitate the interpretation of data, and condense information. Interest in learning for students is an important factor for the successful achievement of learning objectives. Due to the lack of interest will grow the passion to learn and a sense of fun to the subject. Conversely the absence of strong interest, the desire or curiosity also lost and will lead to failure.Keywords: Â Learning Media, Learning Motivation, Learning Fiqh